Single photon ionization of van der Waals clusters with a soft x-ray laser: (CO2)n and (CO2n(H2O)m - Heinbuch, S., author; Rocca, Jorge J., author; Dong, F., author; Bernstein, E. R., author; American Institute of Physics, publisher (Colorado State University. Libraries, 2006)
Pure neutral (CO2)n clusters and mixed (CO2)n(H2O)m clusters are investigated employing time of flight mass spectroscopy and single photon ionization at 26.5 eV. The distribution of pure (CO2)n clusters decreases roughly exponentially with increasing cluster size. During the ionization process, neutral clusters suffer little fragmentation because almost all excess cluster energy above the vertical ionization energy is taken away by the photoelectron and only a small part of the photon energy is deposited into the (CO2)n cluster. Metastable dissociation rate constants of (CO2)n+ are measured in the range of (0.2-1.5) × 104 s−1 for cluster sizes of 5≤n≤16. Mixed CO2-H2O clusters are studied under different generation conditions (5% and 20% CO2 partial pressures and high and low expansion pressures). At high CO2 concentration, predominant signals in the mass spectrum are the (CO2)n+ cluster ions. The unprotonated cluster ion series (CO2)nH2O+ and (CO2)n(H2O)2+ are also observed under these conditions. At low CO2 concentration, protonated cluster ions (H2O)nH+ are the dominant signals, and the protonated CO2(H2O)nH+ and unprotonated (H2O)n+ and (CO2) × (H2O)n+ cluster ion series are also observed. The mechanisms and dynamics of the formation of these neutral and ionic clusters are discussed.